A novel GSN variant outside the G2 calcium‐binding domain associated with Amyloidosis of the Finnish type. Issue 7 (11th May 2021) - Mullany, Sean; Souzeau, Emmanuelle; Klebe, Sonja; Zhou, Tiger; Knight, Lachlan S. W.; Qassim, Ayub; Berry, Ella C.; Marshall, Henry; Hussey, Matthew; Dubowsky, Andrew; Breen, James; Hassall, Mark M.; et al.
Abstract: Gelsolin ( GSN ) variants have been implicated in amyloidosis of the Finnish type. This case series reports a novel GSN :c.1477T>C, p.(Trp493Arg) variant in a family with ocular and systemic features consistent with Finnish Amyloidosis. Exome sequencing performed on affected individuals from two families manifesting cutis laxa and polymorphic corneal stromal opacities demonstrated the classic GSN :c.654G>A, p.Asp214Asn variant in single affected individual from one family, and a previously undocumented GSN :c.1477T>C variant in three affected first‐degree relatives from a separate family. Immunohistochemical studies on corneal tissue from a proband with the c.1477T>C variant identified gelsolin protein within histologically defined corneal amyloid deposits. This study reports a novel association between the predicted pathogenic GSN :c.1477T>C variant and amyloidosis of the Finnish type, and is the first to provide functional evidence of a pathological GSN variant at a locus distant to the critical G2 calcium‐binding region, resulting in the phenotype of amyloidosis of the Finnish type. Abstract : Corneal opacities in an individual harboring the novel pathogenic GSN:c1477T>C variant